(untitled) (Cahiers Africains de rhétorique, 2025)
The objective of this article is to show that Robert Desnos, through his surrealist vision, experiences on the unconscious and the imagination the objects present in his environment, and in particular plants. He therefore perceives the plant species of the forest as beings endowed with living souls. As a result, forest plants have the power of reflection, thought and locomotion like humans. They can in fact think, communicate and move at will like moving living beings. Thus, of all the linguistic resources contained in the texts of the corpus studied, the mentality of plants as well as their power of locomotion constitute the main objects of this reflection. Linguistics of the text, literary psychoanalysis, eco-semiotics and ecopoetics, or ecocriticism constitute theoretical approaches likely to lead to a scientific and objective reading of the corpus selected.